Thrombotic Microangiopathy in Cancer - Weitz, Ilene Ceil (Seminars in Thrombosis and Hemostasis, 2019)
Thrombotic microangiopathy (TMA) is a rare but often devastating complication of cancer and cancer treatment. The syndrome is defined by thrombocytopenia (i.e., a platelet count of < 150,000/mcL or > 30% decrease from baseline), microangiopathic hemolytic anemia, and some evidence of organ damage. Among the nine recognized groups of disorders causing TMA, the focus of this article will be on cancer and cancer treatment-related causes of TMA. This review will discuss the pathophysiology of TMA in cancer, chemotherapy-associated TMA, transplant-associated TMA, and newer therapeutic modalities.
Keywords: thrombotic microangiopathy; cancer; hematopoietic stem cell transplantation; eculizumab